2013
DOI: 10.1039/c3cp52734d
|View full text |Cite
|
Sign up to set email alerts
|

First principles prediction of an insensitive high energy density material

Abstract: A new high performance yet insensitive explosive is proposed, based on an extensive computational study of tris(tetrazolyl)amine in the solid state and in the gas phase. The calculations for the solid state employ the PBE density functional with empirical dispersion correction while the gas phase calculations use the higher level of B3LYP and MP2. Two stable crystalline structures of tris(tertrazolyl)amine were located belonging to P1 and P21 space groups. The crystal structures obtained reveal that solid tris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 69 publications
2
19
1
Order By: Relevance
“…Most effective molecular HEDM contain nitrogen-and oxygen-containing heterocycles and/or NOx moieties [10]. The decomposition of such molecules usually leads to the release of COx, NOx and cyanogen molecules which are toxic or environmentally damaging [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most effective molecular HEDM contain nitrogen-and oxygen-containing heterocycles and/or NOx moieties [10]. The decomposition of such molecules usually leads to the release of COx, NOx and cyanogen molecules which are toxic or environmentally damaging [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Also desired are low cost of inputs and of synthesis as well as low environmental impact of both inputs and the products of decomposition. New HEDMs are actively researched experimentally as well as computationally [2][3][4][5][6][7][8][9]. Most effective molecular HEDM contain nitrogen-and oxygen-containing heterocycles and/or NOx moieties [10].…”
Section: Introductionmentioning
confidence: 99%
“…The impact sensitivity as the most commonly used method for assessing sensitivities of explosives is measured by the drop height h 50% , and the shorter the drop height, the greater the impact sensitivity. It has been found that impact sensitivity has several strong correlations with various molecular properties . Using 4 empirical models on the basis of the properties of electrostatic potential and the heat of detonation, as proposed by Rice and Hare, the h 50% were estimated and the results are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The impact sensitivity is the most common method of assessing sensitivities of an explosive and measured by the drop height h 50% , and the shorter the drop height, the greater the impact sensitivity . All previous works about impact sensitivity of explosives have revealed the existence of several series of relationships with the predicted molecular properties . Using the empirical models based on the properties of electrostatic potential and heat of detonation, as suggested by Rice and Hare, the h 50% were estimated and the results are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…[48,49] All previous works about impact sensitivity of explosives have revealed the existence of several series of relationships with the predicted molecular properties. [33,44,[50][51][52][53] Using the empirical models based on the properties of electrostatic potential and heat of detonation, as suggested by Rice and Hare, [44] the h 50% were estimated and the results are listed in Table 4.…”
Section: Stability and Sensitivitymentioning
confidence: 99%